KOMPARASI PENAFSIRAN AYAT-AYAT PERNIKAHAN BEDA AGAMA (TAJDID: Jurnal Ilmu Ushuluddin, 2019)
Muhammad Abduh and Ahmad Mustafa al-Maraghi are teachers and students. As a student of Muhammad Abduh, of course Mustafa al-Maraghi has many similarities. Uniquely, even though the similarities are more prominent, the interpretation of al Maraghi seems more acceptable, considered to be more straightforward, rather than the interpretation produced by Rashid Ridho and his teacher. Regarding the verse above, their interpretation tends to be different. Based on this fact, the authors are interested in examining further how the interpretations of Muhammad Abduh and Mustafa al-Maraghi as modern Mufassir are related to the legal verses in the Qur'an regarding the issue of interfaith marriage. Then the author will do a comparative analysis of their opinions or the results of the methods they use in their interpretation. the author only focuses on the interpretation of interfaith marriage verses in surah al Baqarah 221 and al Maidah 05 according to the interpretation of al-Manar and the interpretation of al-Maraghi. But these two verses are supported by verse 10 of Surat al Mumtahanah.Muhammad Abduh dan Ahmad Mustafa al-Maraghi adalah seorang guru dan murid. Sebagai seorang murid Muhammad Abduh, tentu saja Mustafa al-Maraghi mempunyai banyak persamaan. Uniknya, meski persamaannya lebih menonjol, namun tafsir al Maraghi tampaknya lebih dapat diterima, dianggap lebih lurus, daripada tafsir yang dihasilkan Rasyid Ridho dan gurunya. Terkait ayat di atas, penafsiran mereka cenderung berbeda. Berdasarkan fakta ini, penulis tertarik untuk  mengkaji lebih jauh bagaimana penafsiran Muhammad Abduh dan Mustafa al-Maraghi selaku Mufassir modern terkait ayat-ayat hukum dalam al-Qur’an terkait masalah pernikahan beda agama. Kemudian penulis akan melakukan analisis komparasi terhadap pendapat mereka atau hasil dari metode yang mereka pakai dalam penafsiran mereka. penulis hanya memfokuskan penelitian terhadap penafsiran tentang ayat-ayat nikah beda agama  dalam surah al Baqarah 221 dan al Maidah 05 menurut tafsir al-Manar dan tafsir al-Maraghi.  Tetapi dua ayat tersebut didukung oleh ayat 10 surat al Mumtahanah.